Managing stress : principles and strategies for health and well-being - Seaward, Brian Luke (Jones & Bartlett Learning, 2012)
Managing Stress, Seventh Edition, Provides A Comprehensive Approach To Stress Management Honoring The Integration, Balance, And Harmony Of Mind, Body, Spirit, And Emotions. The Holistic Approach Taken By Internationally Acclaimed Lecturer And Author Brian Luke Seaward Gently Guides The Reader To Greater Levels Of Mental, Emotional, Physical, And Spiritual Well Being By Emphasizing The Importance Of Mind Body Spirit Unity. Referred To As The Authority On Stress Management By Students And Professionals, This Book Gives Students The Tools Needed To Identify And Manage Stress While Teaching Them How To Strive For Health And Balance. --Amazon.com